2015
DOI: 10.1002/2014jd022848
|View full text |Cite
|
Sign up to set email alerts
|

A negative phase shift of the winter AO/NAO due to the recent Arctic sea‐ice reduction in late autumn

Abstract: This paper examines the possible linkage between the recent reduction in Arctic sea-ice extent and the wintertime Arctic Oscillation (AO)/North Atlantic Oscillation (NAO). Observational analyses using the ERA interim reanalysis and merged Hadley/Optimum Interpolation Sea Surface Temperature data reveal that a reduced (increased) sea-ice area in November leads to more negative (positive) phases of the AO and NAO in early and late winter, respectively. We simulate the atmospheric response to observed sea-ice ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
165
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 204 publications
(194 citation statements)
references
References 66 publications
15
165
2
Order By: Relevance
“…These events can weaken, or even reverse, the stratospheric winds, leading to an eventual downward propagation of the circulation feature into the troposphere 86 and a tendency for a negative phase of the AO. This mechanism establishes memory in the system, as sea ice loss and snow cover in late autumn can affect the tropospheric jet stream in late winter through lagged transfer of wave-induced disturbances involving the stratosphere 39 . Only models with realistic stratospheres are able to capture this mechanism.…”
Section: Living With An Uncertain Climate Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…These events can weaken, or even reverse, the stratospheric winds, leading to an eventual downward propagation of the circulation feature into the troposphere 86 and a tendency for a negative phase of the AO. This mechanism establishes memory in the system, as sea ice loss and snow cover in late autumn can affect the tropospheric jet stream in late winter through lagged transfer of wave-induced disturbances involving the stratosphere 39 . Only models with realistic stratospheres are able to capture this mechanism.…”
Section: Living With An Uncertain Climate Systemmentioning
confidence: 99%
“…Often climate models and correlation analyses of observations produce differing estimates of how the climate will respond to the ongoing AA and loss of sea ice 48,58 . For example, climate model studies have reported shifts towards both the positive or negative phases of the AO and/or NAO, or no apparent shift, in response to AA 13,19,34,39,59 . Analyses that involve averaging over large areas, long time periods and/or many ensemble members may not reveal specific atmospheric responses to AA, such as enhanced jet stream ridges and troughs that occur in specific locations.…”
Section: Living With An Uncertain Climate Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of works relating anomalously low summer-autumn sea-ice-cover in the Arctic to severe winters over Northern Eurasia and North America based on both reanalysis data and model results analysis (e.g., [7,8]; review articles by Cohen et al [9][10][11]). Most evidence has been found for dynamical pathways in the troposphere and in the stratosphere, resulting in more frequent occurrence of the negative phase of the Arctic Oscillation (AO) or North Atlantic Oscillation (NAO) in late winter (e.g., [5,12,13]). Due to additional heat uptake by the larger sea-ice-free areas in summer and early autumn, the refreezing in autumn is delayed.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced upward propagating planetary waves may lead to wave breaking in the polar stratosphere, which in turn may weaken the polar vortex (e.g., [16,17]). The downward propagation of these stratospheric circulation anomalies may start in mid-winter and can contribute to the persistent negative NAO/AO anomalies in mid-winter to late winter [13,16,18].…”
Section: Introductionmentioning
confidence: 99%